PENGARUH METODE SIMULASI DAN DEMONSTRASI TERHADAP KEMAMPUAN MENYIKAT GIGI PADA SISWA SDN GUE GAJAH ACEH BESAR - Mardelita, Sisca; Keumala, Cut Ratna; Aprillia, Ayu (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
The proportion of Acehnese who experience dental and oral health problems is 56%, and correct brushing behavior is only 2.9%. Aceh Besar shows the prevalence of people experiencing caries which reaches 44.23% and Darul Imarah Aceh Besar Health Center based on data on visits of children 6-14 years old who came to the dental poly in 2019 with caries cases of 0.037%. The purpose of the study was to determine the effect of dental and oral health counseling with simulation and demonstration methods on the ability to brush children's teeth at SD Negeri Gue Gajah Aceh Besar Regency in 2021. This research is a quasi-experimental research design one group pretest-posttest design. The population of all grade V students of SD Negeri Gue Gajah Aceh Besar Regency is 30 students. The study was conducted on the 29th March- April 10, 2021. The instrument used is a pretest-posttest observation sheet. Results based on paired t-tests produce a p value = 0.001 (p<0.05) which means less than 0.05. Based on the research findings, it can be concluded that the use of simulation and demonstration methods in dental and oral health education has an impact on students' brushing ability.